The Study on Preparation of Japanese Encephalitis DNA Vaccine - Ri, Chang Guk; Song, Yong Su; Hyon, Kyong Hui; Ri, Won Chol; Pak, Su Il; Choe, Tong Il; Kim, Ryong Sik (Medical Science Journal for Advance Research, 2026)
The major immune antigen gene (JEV E) of JEV was synthesized by RT-PCR and cloned into the eukaryotic expression vector, pVAX1 to prepare recombinant plasmid pVAX-JEV E that could be used as a japanese encephalitis DNA vaccine. In mice (immune groups) vaccinated twice im at 2 weeks intervals with 10 or 50㎍ of JEV DNA vaccine, the antibody titers were 1:160-1:320 and survival rate were 42.8~83.3%. A few mild adverse events were observed in volunteers vaccinated twice with 0.5 mg of JEV DNA vaccine and the antibody titer in vaccines were 1:80 to 1:160 at 2~4 weeks after immunization.